Avaliação da capacidade funcional em idosos que praticam treinamento funcional - MOREIRA, Marcelo Hideo Okada (2020)
Currently, the elderly seek physical activity, not only for physical benefits, but also those related to mental health, in which they provide help in the self-esteem of the elderly, making the elderly more participative in personal and social life. Thus, this study aimed to evaluate the balance and functional capacity in elderly women practicing and elderly and not practicing functional training. In order to do so, it was done through the Mini Mental State Examination and through the sit-and-raise tests in 30 seconds, Time-up and go, Tinetti scale and LawtonBrody scale, as well as socio-demographic data. Fifteen elderly women (60 to 70 years old) and 15 non-practicing elderly women (71 to 80 years old) were evaluated. In the comparison of the tests between the practicing and non-practicing elderly women, the response scores were similar, and the older women performed the task more often suggesting more limb strength for the Timed up and go test. Non-adherent older women were at greater risk for falls and for the Lawton-Brody scale, and there was a relationship of perceived health status with the Timed up and go test for the elderly, showing that the possibility of a fall risk influences health status the same. Thus, it can be inferred that future studies are indispensable for health promotion and disease prevention, which can minimize factors that interfere with functional capacity, promoting greater autonomy and quality of life for this social follow-up.